Dietary fatty acids and inflammation in the vertebral column of Atlantic salmon, Salmo salar L., smolts: a possible link to spinal deformities - L Gil Martens; E J Lock; P G Fjelldal; A Wargelius; P Araujo; B E Torstensen; P E Witten; T Hansen; R Waagbø; R Ørnsrud (Journal of Fish Diseases, 2010)
Vegetable oils (Vo) are an alternative to fish oil (Fo) in aquaculture feeds. This study aimed to evaluate the effect of dietary soybean oil (Vo diet), rich in linoleic acid, and of dietary fish oil (Fo diet) on the development of spinal deformities under bacterial lipopolysaccharide (LPS)‐induced chronic inflammation conditions in Atlantic salmon, Salmo salar L. Fish [25 g body weight (BW)] were fed the experimental diets for 99 days. On day 47 of feeding (40 g BW), fish were subjected to four experimental regimes: (i) intramuscular injections with LPS, (ii) sham‐injected phosphate‐buffered saline (PBS), (iii) intraperitoneally injected commercial oil adjuvant vaccine, or (iv) no treatment. The fish continued under a common feeding regime in sea water for 165 more days. Body weight was temporarily higher in the Vo group than in the Fo group prior to immunization and was also affected by the type of immunization. At the end of the trial, no differences were seen between the dietary groups. The overall prevalence of spinal deformities was approximately 14% at the end of the experiment. The Vo diet affected vertebral shape but did not induce spinal deformities. In groups injected with LPS and PBS, spinal deformities ranged between 21% and 38%, diet independent. Deformed vertebrae were located at or in proximity to the injection point. Assessment of inflammatory markers revealed high levels of plasma prostaglandin E 2 (PGE 2 ) in the Vo‐fed and LPS‐injected groups, suggesting an inflammatory response to LPS. Cyclooxigenase 2 (COX‐2) mRNA expression in bone was higher in fish fed Fo compared to Vo‐fed fish. Gene expression of immunoglobulin M (IgM) was up‐regulated in bone of all LPS‐injected groups irrespective of dietary oil. In conclusion, the study suggests that Vo is not a risk factor for the development of inflammation‐related spinal deformities. At the same time, we found evidence that localized injection‐related processes could trigger the development of vertebral body malformations.